Achievement Motivation Training for University Students: Effects on Affective and Cognitive Achievement Motivation. - Elias, Habibah; Abdul Rahman, Wan Rafaei (Universiti Putra Malaysia Press, 1994)
This study investigated the effectiveness of an achievement motivation training in increasing the level of achievement motivation of university students. An achievement motivation training was designed to include the teaching of achievement motivation, self-study, planning and goal-setting and motivational garnes. The subjects were 188 second and third year Arts students from a local university selected on their achievement motivation scores measured by the Thematic Apperception Test. The subjects (N=188) were randomly assigned to one of three groups. The achievement motivation group was given the achievement motivation training, the discussion group was given an alternative treatment and the control group was not given any treatment.The results indicated that the group which received the achievement motivation training demonstrated a significant increase in the affective aspect of achievement motivation (p <.05) compared to the discussion group and the control group. The achievement motivation group also showed a significant increase in the cognitive aspect of achievement motivation (p <.05) compared to the discussion group and the control group.